Voodoo - Kristos, Kyle. (Philadelphia : Lippincott, 1976)
Traces the origins, cults, and practices which surround voodooism including voodoo practices in the United States and modern Haiti.
Includes index.
Bibliography: p. 108.
Keywords: Vodou -- Juvenile literature; Vodou